Layer-specific arterial micromechanics and microstructure: Influences of age, anatomical location, and processing technique. (9th May 2019) - Rafuse, Michael; Xu, Xin; Stenmark, Kurt; Neu, Corey P.; Yin, Xiaobo; Tan, Wei
Abstract: The importance of matrix micromechanics is increasingly recognized in cardiovascular research due to the intimate role they play in local vascular cell physiology. However, variations in micromechanics among arterial layers (i.e. intima, media, adventitia), as well as dependency on local matrix composition and/or structure, anatomical location or developmental stage remain largely unknown. This study determined layer-specific stiffness in elastic arteries, including the main pulmonary artery, ascending aorta, and carotid artery using atomic force indentation. To compare stiffness with age and frozen processing techniques, neonatal and adult pulmonary arteries were tested, while fresh (vibratomed) and frozen (cryotomed) tissues were tested from the adult aorta. Results revealed that the mean compressive modulus varied among the intima, sub-luminal media, inner-middle media, and adventitia layers in the range of 1–10 kPa for adult arteries. Adult samples, when compared to neonatal pulmonary arteries, exhibited increased stiffness in all layers except adventitia. Compared to freshly isolated samples, frozen preparation yielded small stiffness increases in each layer to varied degrees, thus inaccurately representing physiological stiffness. To interpret micromechanics measurements, composition and structure analyses of structural matrix proteins were conducted with histology and multiphoton imaging modalities including second harmonic generation and two-photon fluorescence. Composition analysis of matrix protein area density demonstrated that decrease in the elastin-to-collagen and/or glycosaminoglycan-to-collagen ratios corresponded to stiffness increases in identical layers among different types of arteries. However, composition analysis was insufficient to interpret stiffness variations between layers which had dissimilar microstructure. Detailed microstructure analyses may contribute to more complete understanding of arterial micromechanics.